Shifting Paradigms in Carbon Pricing - Brigitte Knopf; Kerstin Burghaus; Christian Flachsland; Michael Jakob; Nicolas Koch; Ottmar Edenhofer (Intereconomics, 2018)
The first pillar of the old paradigm of carbon pricing is the assumption that an emissions trading scheme is the most cost-efficient way to achieve a certain emission reduction target. However, it has become obvious that the old paradigm is unable to solve a number of challenges, e.g. market participants' myopia.
Keywords: 330